Transcription Coactivator BCL3 Acts as a Potential Regulator of Lipid Metabolism Through the Effects on Inflammation - Zhang S (Dove Medical Press, 2021)
Shuo Zhang,1 Jingtao Gao,1 Shibo Liu,1 Lu Yu,1 Wen Zhang,1 Yinming Liang,1,2 Hui Wang1,2 1Henan Key Laboratory of Immunology and Targeted Drug, School of Laboratory Medicine, Xinxiang Medical University, Xinxiang, Henan Province, 453003, People’s Republic of China; 2Henan Collaborative Innovation Center of Molecular Diagnosis and Laboratory Medicine, Xinxiang Medical University, Xinxiang, Henan Province, 453003, People’s Republic of ChinaCorrespondence: Hui WangHenan Key Laboratory of Immunology and Targeted Drug, School of Laboratory Medicine, Xinxiang Medical University, Xinxiang, Henan Province, 453003, People’s Republic of ChinaTel/Fax +86 373 3831203Email wanghui@xxmu.edu.cnBackground and Purpose: Transcriptional coactivator B-cell lymphoma-3 (BCL3) is a member of the IκB family of NF-κB inhibitors and regulates the activity of the NF-κB pathway. However, the relationship between BCL3 and lipid metabolism remains unclear. The present study investigates the effects of BCL3 in immune and metabolism in obese mice.Animals and Methods: Construct Bcl3-KO mice through CRISPR/Cas9 technology. Obesity model was induced in Bcl3-KO mice by feeding a high-fat diet for 16 weeks, and some metabolic-related indicators were analysed.Results: The results showed that the KO mice gained significantly less body weight on a high fat diet without a change in food intake. There was significant improvement in hepatic steatosis and adipose tissue hypertrophy in KO mice. The expression of SREBP1 and its downstream fatty acid synthetase FAS and ACC were down-regulated in KO mice, and the inflammation in adipose tissue and liver was further reduced.Conclusion: These results suggest that BCL3 may be a novel factor in regulating lipid metabolism in the development of obesity.Keywords: inflammation, obesity, BCL3, lipid metabolism, SREBP1